PENYELESAIAN KLAIM PRULINK (PRUDENTIAL UNIT LINK) DI PT. PRUDENTIAL LIFE ASSURANCE PEKANBARU - Amelia, Sri Ayu; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
insurance has two types of insurance namely health insurance and life insurance. Health insurance is one of the insurance products that have several categories. The main categories of health insurance are income disability insurance, assuming traditional medical costs. Furthermore life insurance is a socioeconomic tool, which is the way of a group of people to be able to work together to reduce the burden due to the premature death of the members of the group. In insured life insurance is caused by death (death). Such deaths result in the loss of income of a person or a particular family. Risks that may arise in life insurance mainly lies in the "element of time (time), because it is difficult to know when someone dies. To minimize the risk, it should be held a life insurance. The purpose of writing thesis namely: first, To know the forms of event that can cause rights for the insured involved in prudential links to file claims in PT. Prudential Life Assurance Pekanbaru. Second, To know the things that become obstacles implementation of insurance claims in PT. Prudential Life Assurance Pekanbaru. Third To know the legal protection of the insured who filed a claim in prudential link at PT. Prudential Life Assurance Pekanbaru. This type of research can be classified in the type of juridical sociological legal research and data collected by seeking information based on questionnaires, interviews and literature related to the research. This research was conducted at Datuk Rubiah market Kota Bagansiapiapi whereas population and sample were all parties related to the problem under study. In this study the data used, in this study is by observation, interview and literature study From the research results of the problem there are two main things that can be concluded, firstly, the forms of the event that can be claimed by the insured is because of the events that occur it causes losses, such as the accidental fire, the occurrence of accidents and death before the appointed time of the agreement. Keywords: Arusansi- Claim-Prudential Unit Link